Antimicrobial investigation of selected soil actinomycetes isolated from unexplored regions of Kashmir Himalayas, India. (September 2017) - Shah, Aabid Manzoor; Shakeel-u-Rehman; Hussain, Aehtesham; Mushtaq, Saleem; Rather, Muzafar Ahmad; Shah, Aiyatullah; Ahmad, Zahoor; Khan, Inshad Ali; Bhat, Khursheed Ahmad; Hassan, Qazi Parvaiz
Abstract: The aim of the present study was to isolate and evaluate the antimicrobial potential of soil actinomycetes of Kashmir Himalayas. The secondary metabolites of actinomycetes are the prominent source of antibiotics. A total of 121 morphologically different actinomycete strains were isolated and screened for antimicrobial activity against various human pathogens. The ethyl acetate extract of fermented broth an actinomycete strain, identified as Streptomyces pratensis exhibited significant antimicrobial activity against Staphylococcus aureus ATCC 29213 with MIC 0.25 μg/ml and Mycobacterium tuberculosis Strain H37R v with MIC 0.062 μg/ml. The strain S. pratensis IIIM06 was grown on large scale and their broth was extracted with ethyl acetate. The extract was subjected to various chromatography techniques which led to the isolation of four compounds whose structures were established as actinomycin C1, actinomycin C2, actinomycin C3 and actiphenol on the basis of spectral data analysis. Actinomycin C1, C2 and C3 exhibited potent antimicrobial activity against S. aureus as well as M. tuberculosis . The isolated indigenous actinomycetes exhibited good antibacterial activity and the study reveals that IIIM06 is a promising strain and could be of great potential for industrial applications. Highlights: Isolation of actinomycetes from soil samples collected from Kashmir region of Northwestern Himalayas. Screening of isolated actinomycetes for antimicrobial activity. Identification and phylogenetic analysis of potent Strain (IIIM06). Isolation and Structure Elucidation of the Bioactive Compound from the Streptomyces pratensis IIIM06. Antimicrobial activity of purified compound.